MENCEGAH PENIPUAN DI PERUSAHAAN KELAPA SAWIT: MENJELAJAHI KERANGKA HUKUM DAN SISTEM PENGAWASAN - Rahmatsyah, Rahmatsyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Palm oil companies generate significant profits, making them susceptible to crimes, including fraud. The aim of this research is to understand the regulations regarding fraud in private companies (palm oil companies) and to examine the use of supervisory systems within the Indonesian legal system. This study is conducted using a normative juridical approach. The research findings indicate that there are legal provisions for addressing fraudulent activities in both the public and private sectors (such as palm oil companies). The surveillance system also needs to be implemented by conducting covert observations, unbeknownst to the employees, in order to obtain genuine information. This is done as one of the efforts to control fraud